2012
DOI: 10.1161/hypertensionaha.111.178194
|View full text |Cite
|
Sign up to set email alerts
|

Altered Vascular Resistance Properties and Acute Pressure-Natriuresis Mechanism in Neonatal and Weaning Spontaneously Hypertensive Rats

Abstract: Abstract-Although it has been extensively scrutinized, the factor(s) involved in the initiation and development of hypertension in spontaneously hypertensive rats (SHRs) remains unresolved. The objective of the present study was to determine whether, early in development, the causal mechanism(s) for the development of hypertension in young SHRs involves an integration of 2 processes, specifically an upregulation of structurally based vascular resistance properties and a rightward shift in the hemodynamic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
10
0
2
Order By: Relevance
“…A raised SVR suggests relative resistance vessel constriction and reduced density of small resistance arteries. Neither was measured directly here, but vasoconstriction and reduced small arterial density are consistent with reports in models of hypertension from animals 28 and in humans. 29 The relationship between higher SVR and smaller LVOT (Figure 1) may arise from structural or from additional physiological factors.…”
Section: Systemic Vascular Resistancesupporting
confidence: 88%
“…A raised SVR suggests relative resistance vessel constriction and reduced density of small resistance arteries. Neither was measured directly here, but vasoconstriction and reduced small arterial density are consistent with reports in models of hypertension from animals 28 and in humans. 29 The relationship between higher SVR and smaller LVOT (Figure 1) may arise from structural or from additional physiological factors.…”
Section: Systemic Vascular Resistancesupporting
confidence: 88%
“…Moreover, recent work by Komolova et al showed vascular changes are evident as early as 3 weeks of age, 5 implicating the period before weaning as an important determinant in the development of hypertension in this model.…”
Section: Discussionmentioning
confidence: 58%
“…However, there was a small but significant increase in resting heart rate in vivo in the prehypertensive SHR. Previous studies have also demonstrated no difference in arterial blood pressure between the SHR and WKY at 4 -5 wk of age using the noninvasive tail-cuff method (15,33) and also following surgical implantation of a radiotelemetry device (16). While the telemetry study reports a significant tachycardia in the SHR, reports from tail-cuff data vary from a significant tachycardia being observed in the WKY (15) to a tachycardia being observed in the SHR (33).…”
Section: Discussionmentioning
confidence: 92%